Розробка авто-кормушки для домашніх тварин - Щиковська, О. О. (ХНУРЕ, 2023)
The functionality of this tool is intended to make life easier for cat owners who have difficulty feeding their pets when they are not at home. This cat feeding tool will work automatically, after writing a program with the task of feeding time and dosage, it uses a stepper motor to open the food containers according to the predetermined time. Such a tool can be especially useful for cat owners who have erratic schedules or travel on weekends and holidays. An added advantage is that it can be set up for multiple feedings per day, ensuring enough food for cats throughout the day. This tool can also be a helpful solution for cats who require a special diet, as it allows for precise control over the amount and timing of their meals.
Keywords: Автоматична годівниця; ARDUINO NANO